Inadequate Support for Social Mental Health in Iran’s Criminal Policy and Macro-Strategic Policy Documents - Khaghani Esfahani, Mahdi (Bioethics and Health Law Journal (BHL), 2026)
Support for social mental health, despite its central role in preventing Social harms and criminal involvement, occupies a marginal and unstable position in Iran’s public policymaking. This article critically examines the high-level policy documents of the Islamic Republic of Iran - specifically the General Policies of the Islamic Republic of Iran and Iran's Overall Vision Document for 2024, selected five-year Development Plans adopted from the early 1380s through the late (2000s-2010s) and annual budget laws enacted during the 1390s and early (2010s-early 2020s) - in order to assess the extent and quality of attention devoted to social mental health within Iran’s criminal policy framework. The study adopts a qualitative, interdisciplinary analytical approach, focusing on the conceptual and institutional linkages between criminal policy and social mental health as reflected in upstream policy texts and their modes of implementation. The findings demonstrate that references to social mental health in these documents are largely indirect, abstract and non-binding, often subsumed under vague notions such as “social harms”, “spiritual health” or limited support for chronic psychiatric patients. This marginalization is further intensified in budgetary legislation within the above period, where mental health is not treated as a rights-based public policy with a defined basic service package and a transparent, independent funding line, but rather as a fragmented, project-based expenditure dependent on annual fiscal conditions. The inconsistency between macro-level policy commitments - particularly the emphasis on prevention and mental health promotion in general health policies - and the treatment-oriented, short-term logic governing budget allocations has weakened social prevention mechanisms and shifted the burden of unmanaged mental health issues onto the criminal justice system. The article concludes that inadequate support for social mental health in high-level policy documents and related budget laws during the examined period represents not merely a shortcoming in public health governance, but a structural deficiency in criminal policy. This configuration reinforces reactive, stigmatizing and security-oriented responses, contributes to the reproduction of crime, increases penal costs and undermines social justice. Repositioning social mental health within upstream policy frameworks and budgetary structures is therefore essential for aligning criminal policy with preventive and health-oriented approaches.